Training Of Volleyball Players In Various Age Groups - Kazakov A.R (Peerian Journals Publishing, 2025)
This article discusses scientific opinions about the types of training and preparations, methods and in the preparation of volleyball players in different age groups
Keywords: volleyball; training; competition